53x-17-9x=18+44x-35

Simple and best practice solution for 53x-17-9x=18+44x-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53x-17-9x=18+44x-35 equation:


Simplifying
53x + -17 + -9x = 18 + 44x + -35

Reorder the terms:
-17 + 53x + -9x = 18 + 44x + -35

Combine like terms: 53x + -9x = 44x
-17 + 44x = 18 + 44x + -35

Reorder the terms:
-17 + 44x = 18 + -35 + 44x

Combine like terms: 18 + -35 = -17
-17 + 44x = -17 + 44x

Add '17' to each side of the equation.
-17 + 17 + 44x = -17 + 17 + 44x

Combine like terms: -17 + 17 = 0
0 + 44x = -17 + 17 + 44x
44x = -17 + 17 + 44x

Combine like terms: -17 + 17 = 0
44x = 0 + 44x
44x = 44x

Add '-44x' to each side of the equation.
44x + -44x = 44x + -44x

Combine like terms: 44x + -44x = 0
0 = 44x + -44x

Combine like terms: 44x + -44x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 53x-179x=18+44x-35 | | y=3x^2-15x-12 | | -5=x^2+4x | | 6x^6+6x-24= | | 2-4[4-(2y-5)]= | | 5000=(x+50)x | | 6x-3=(-4x+3) | | xb-6=cx+4 | | K/3-18=-26 | | 5*-5*25-5= | | 15x-10=6x-(x+2)+(3-x) | | -16x^2+78x+6=0 | | bx-6=cx+4 | | -8=3/7x | | h+2(h-6)=18 | | 10x+4y+5z=170 | | 4(x+3)=6(2x-5) | | -7/4c=-7 | | F(7)-f(4)/7-4 | | -18=2/3x | | 3(x+7)=6(-3+7x) | | -5/6d=5 | | (1.6x^3+4.9x^2-3.7x)-(-4.1x^3-4.8x^2+95)= | | Q=t/12 | | 0.5a-3=7-3/4a | | 5(2x-2)=5(x-1) | | 7u+5+18u+18=248 | | -7(2x-5)+5(3x-5)-2=6-9 | | 21+1.5h=10+2.75h | | (-1/6x^6)(-1/5x) | | -7(2x-5)+(3x-5)=6-9 | | 90=18y+30-5y-5 |

Equations solver categories